Analisis Sistematis Pengelolaan Keuangan pada Satuan Pendidikan Dasar dalam Kerangka Manajemen Berbasis Sekolah - Benedictus Melandri Aristo Putra; Sri Marmoah (ARZUSIN, 2026)
Schools’ readiness in financial management remains suboptimal, thereby affecting the effectiveness of implementing School-Based Management (SBM). This study aimed to analyze the challenges, best practices, and optimization strategies for school financial management within the SBM framework. This study used the Systematic Literature Review (SLR) method by referring to the PRISMA protocol. Data were obtained from the Google Scholar and Scopus databases, covering publications from 2019 to 2025. A total of 12 articles that met the inclusion criteria were analyzed using thematic analysis techniques. The results showed that the main challenges in school financial management include limited and delayed funding, low human resource competence, bureaucratic complexity, and weak transparency and public participation. The best practices identified include participatory budget planning, digitalization of financial reporting, regular monitoring and evaluation, and strengthening partnerships with stakeholders. Thus, optimizing financial management in SBM requires synergy among human resource capacity building, technology utilization, procedural simplification, and the strengthening of transparency and accountability. These findings provide practical contributions for schools and policymakers in improving the quality of educational financial governance to become more effective, transparent, and accountable.